1995
DOI: 10.2214/ajr.164.2.7839965
|View full text |Cite
|
Sign up to set email alerts
|

Hepatobiliary cysts in patients with autosomal dominant polycystic kidney disease: prevalence and CT findings.

Abstract: OBJECTIVE.Hepatobiliary (intrahepatic and peribiliary)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
38
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 4 publications
3
38
0
Order By: Relevance
“…14,15 Although our patient had multiple renal cysts, they did not meet the criteria of an autosomal dominant polycystic kidney disease. He had a daughter who was diagnosed as having IPH.…”
Section: Discussionmentioning
confidence: 74%
“…14,15 Although our patient had multiple renal cysts, they did not meet the criteria of an autosomal dominant polycystic kidney disease. He had a daughter who was diagnosed as having IPH.…”
Section: Discussionmentioning
confidence: 74%
“…These 2 types of cysts can be identified by computed tomography. 21,22 The intrahepatic cysts are within the liver parenchyma but not in contact with the larger portal triads, whereas the peribiliary cysts are adjacent to the larger portal triads or in the hepatic hilum. In our study, both types of cysts were detected radiologically and histologically in patients with isolated ADPLD, suggesting that isolated ADPLD and polycystic liver disease associated with ADPKD have similar pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, multiple hepatic peribiliary cysts have been found in the patients with a variety of liver diseases, such as cirrhosis, hepatocellular carcinoma, portal hypertension, extrahepatic portal venous obstruction, and systemic infection. Moreover, an association with adult-type polycystic disease of liver and kidneys has been reported [7,8], suggesting that some congenital factors might also be associated with the occurrence of peribiliary cysts. Generally, multiple hepatic peribiliary cysts have been considered to be asymptomatic, but some previous reports have indicated that these cysts are not entirely harmless and can even cause obstructive jaundice [3,4,9,10].…”
Section: Discussionmentioning
confidence: 99%